2021
DOI: 10.1128/msystems.00807-21
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Metabolomic and Transcriptomic Analyses Uncover Metabolic Alterations and Pigment Diversity in Monascus in Response to Different Nitrogen Sources

Abstract: Natural MPs containing a mixture of red, orange, and yellow pigments are widely used as food coloring agents. MP diversity provides foods with versatile colors and health benefits but, in turn, complicate efforts to achieve maximum yield or desirable combination of pigments during the manufacturing process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 49 publications
(61 reference statements)
1
5
0
Order By: Relevance
“…With high levels of reducing equivalents, more ATP were synthesized through oxidative respiratory chain, but interestingly, adding oxaloacetate depressed the intracellular ATP level, which might be due to its shunt flux between TCA and EMP. Additionally, by regulating the TCA cycle, we found that gene expression encoding oxidoreductases in Monascus synthesistic gene cluster changed greatly, but it made little contribution to explaining the production change, possibly because gene cluster expression was not the main limiting factor of pigment synthesis under the conditions used in this study, as described previously [ 21 ].…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations
“…With high levels of reducing equivalents, more ATP were synthesized through oxidative respiratory chain, but interestingly, adding oxaloacetate depressed the intracellular ATP level, which might be due to its shunt flux between TCA and EMP. Additionally, by regulating the TCA cycle, we found that gene expression encoding oxidoreductases in Monascus synthesistic gene cluster changed greatly, but it made little contribution to explaining the production change, possibly because gene cluster expression was not the main limiting factor of pigment synthesis under the conditions used in this study, as described previously [ 21 ].…”
Section: Discussionsupporting
confidence: 52%
“…However, the stability of production and product quality of MonAzPs is exclusively critical for Monascus fermentation in industry. Until now, numerous factors, including: pH; temperature; carbohydrates; light; and especially nitrogen sources, such as peptone, yeast powder, ammonium chloride, and ammonium nitrate; have been proved to lead to different effects on MonAzPs production [ 21 ], which undoubtedly complicates the investigation of Monascus fermentation. Hence, a simplified and efficient model, such as metabolic perturbation, is necessary to dissect the metabolic mechanism of MonAzPs biosynthesis and regulation, and aid to establish a high-efficient fermentation regulation strategy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Importantly, comparative transcriptomic analyses have been applied to investigate gene transcription in this fungus under different fermentation conditions (such as different carbon/nitrogen sources, special additives, light treatment, etc.) [ 12 , 13 , 14 , 15 ]. These studies often concentrated on the biosynthesis of MPs, although several reports also investigated the expression of the CIT pathway in different M. purpureus strains and fermentation conditions.…”
Section: Introductionmentioning
confidence: 99%